2015
DOI: 10.1021/acs.orglett.5b00345
|View full text |Cite
|
Sign up to set email alerts
|

Total Synthesis and Structural Revision of Mycalol, an Anticancer Natural Product from the Marine Source

Abstract: The total synthesis of an anticancer (anaplastic thyroid) natural lipid mycalol has been accomplished for the first time. Synthesis of originally proposed structure necessitated the revision of structure in which the position of acetate group moved from C20 to C19 and a change in stereochemistry of the glycerol unit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 35 publications
1
32
0
Order By: Relevance
“…[708][709][710] Chemical examination of adult and bud larvae of the chemically-defended sponge Tethya maza indicated that the sterol composition of both were largely similar, suggesting that the larvae are also defended during reproduction. 711 First total syntheses were reported for many compounds including the lipids motualevic acid F, (E)-and (Z)-antazirine, [712][713][714] mycalol (revised to 1105) [715][716][717] and myrmekioside A, 718,719 and polyacetylenes callyspongynic acid, 720,721 phosphoiodyn A and placotylene A. [722][723][724][725] The structure of plakinidone has been corrected to 1106; the compound is highly sensitive to air oxidation.…”
Section: Spongesmentioning
confidence: 99%
“…[708][709][710] Chemical examination of adult and bud larvae of the chemically-defended sponge Tethya maza indicated that the sterol composition of both were largely similar, suggesting that the larvae are also defended during reproduction. 711 First total syntheses were reported for many compounds including the lipids motualevic acid F, (E)-and (Z)-antazirine, [712][713][714] mycalol (revised to 1105) [715][716][717] and myrmekioside A, 718,719 and polyacetylenes callyspongynic acid, 720,721 phosphoiodyn A and placotylene A. [722][723][724][725] The structure of plakinidone has been corrected to 1106; the compound is highly sensitive to air oxidation.…”
Section: Spongesmentioning
confidence: 99%
“…21 Hydroboration-oxidation reaction of alkene 6 with BH 3 SMe 2 in THF at 0 °C proceeded smoothly to give the diol 13 in 72% yield. 22 The resulting diol was then esterified with MsCl in the presence of Et 3 N and a catalytic amount of DMAP in CH 2 Cl 2 . The crude dimesylate, owing to its instability, was immediately subjected to cyclization with benzylamine at 80 °C to furnish piperidine 5 in 66% yield over two steps.…”
Section: Scheme 1 Retrosynthetic Analysismentioning
confidence: 99%
“…[2] Initial biological studies revealed that mycalol selectively kills human anaplastic thyroid carcinoma (ATC). [3] Subsequently, Goswami et al reported the synthesis of the originally mixture of diastereomers. In 2015, Reddy et al developed an elegant strategy for the synthesis of the proposed structure of mycalol (1) by using Sharpless asymmetric kinetic resolution, Jacobsen kinetic resolution, and cross metathesis as key steps.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, they hypothesized that the correct structure could be 2 (Figure 1), based on a detailed comparison of NMR spectroscopic data, and they confirmed this by total synthesis. [3] Subsequently, Goswami et al reported the synthesis of the originally of nBuLi and HMPA (hexamethylphosphoramide) proceeded smoothly to give compound 16 in good yield (70 %). [14] Partial reduction of the alkyne functionality of 16 under Lindlar hydrogenation conditions [15] (Pd/BaSO 4 , quinoline) followed by oxidative removal of the PMB group with DDQ (2,3-dichloro-5,6-dicyano-1,4-benzoquinone) gave alcohol 5 in 72 % yield over two steps.…”
Section: Introductionmentioning
confidence: 99%